2000
DOI: 10.1046/j.1365-2125.2000.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Ziprasidone and the pharmacokinetics of a combined oral contraceptive

Abstract: Aims To determine whether multiple doses of ziprasidone alter the steady-state pharmacokinetics of the component steroids, ethinyloestradiol and levonorgestrel, of an oral contraceptive; to evaluate the tolerability of a co-administered combined oral contraceptive and ziprasidone; and to compare plasma concentrations of prolactin in subjects taking a combined oral contraceptive with placebo or ziprasidone. Methods Nineteen women taking a combined oral contraceptive (ethinyloestradiol 30 mg day x 1 and levonorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…17 The lack of CYP3A4 inhibition was supported by a lack of an AUC increase following exposure to ethinylestradiol, a CYP3A4 substrate, on coadministration with ziprasidone. 25 The effect of ziprasidone on CYP2D6 activity was assessed by administering ziprasidone 80 mg, placebo, or paroxetine 20 mg (a potent CYP2D6 inhibitor) 2 hours before administering dextromethorphan (a model CYP2D6 substrate). Ziprasidone did not change the urinary ratio of dextromethorphan to dextrophan (dextromethorphan's CYP2D6 primary metabolite) compared with placebo, whereas it was increased 10-fold after paroxetine administration.…”
Section: Drug Interactionsmentioning
confidence: 99%
“…17 The lack of CYP3A4 inhibition was supported by a lack of an AUC increase following exposure to ethinylestradiol, a CYP3A4 substrate, on coadministration with ziprasidone. 25 The effect of ziprasidone on CYP2D6 activity was assessed by administering ziprasidone 80 mg, placebo, or paroxetine 20 mg (a potent CYP2D6 inhibitor) 2 hours before administering dextromethorphan (a model CYP2D6 substrate). Ziprasidone did not change the urinary ratio of dextromethorphan to dextrophan (dextromethorphan's CYP2D6 primary metabolite) compared with placebo, whereas it was increased 10-fold after paroxetine administration.…”
Section: Drug Interactionsmentioning
confidence: 99%
“…Studies performed in vitro using human liver microsomes have shown that the oxidative metabolism of ziprasidone is mediated primarily by CYP3A4 [1]. In vivo studies have demonstrated no clinically significant pharmacokinetic interactions between ziprasidone and cimetidine (which inhibits several isoforms of CYP including CYP3A4), ethinyloestradiol (which is metabolized by CYP3A4), or ketoconazole (a potent inhibitor of CYP3A4), suggesting that co‐administration with other CYP3A4 inhibitors or inducers will not require dose adjustment [2–4].…”
Section: Introductionmentioning
confidence: 99%
“…Carbamazepine (CBZ), which can induce CYP3A4, led to a modest decrease in steady-state exposure to ziprasidone (36%) that was thought to be clinically insignificant [45]. Coadministration of ziprasidone with a combined oral contraceptive containing ethinyloestradiol, a CYP3A4 substrate, indicated no clinically significant effect on the pharmacokinetics of the oral contraceptive [47]. Coadministration of ziprasidone with a combined oral contraceptive containing ethinyloestradiol, a CYP3A4 substrate, indicated no clinically significant effect on the pharmacokinetics of the oral contraceptive [47].…”
Section: Pharmacokineticsmentioning
confidence: 99%